PENGARUH AIR PAYAU TERHADAP KUAT TEKAN BETON - Muhammad Rifaldi; Arifiend Nursandah; Himatul Farichah (AGREGAT, 2022)
ABSTRACTConcrete is a combination of constituent materials which consists of hydraulic cement (portland cement), coarse aggregate, fine aggregate, water, and additives. Generally, the use of concrete starts from the bottom construction to the top construction. In use in under construction, concrete will be in a variety of environments, one of which is an aggressive environment such as brackish water. Brackish water is a mixture of fresh water and sea water (salt water). If the salt content contained in one liter of water is between 0.5 to 30 grams, then this water is called brackish water. The study used brackish water taken from 2 different places, namely Kenjeran brackish water and mangrove brackish water and using experimental methods in the laboratory, with a total of 60 samples of concrete specimens. Testing the compressive strength of concrete at the age of 7 days, 14 days, 21 days, and 28 days, with a cylinder diameter of 15 cm and a height of 30 cm, with a planned concrete quality of f'c = 25 MPaTest results of normal concrete have a compressive strength of 25.93 MPa, the concrete with a mixture of brackish water Kenjeran has a compressive strength of 17.75, the compressive strength decreases by 31.54% from normal concrete, while the concrete with a mixture of mangrove brackish water has a compressive strength of 18.84 MPa, the compressive strength decreases by 27, 36% of normal concrete. The statistical model testing used is the Chi-Square test and the T test using the SPSS application. Keywords: Concrete, brackish water, compressive strength of concrete  ABSTRAKBeton merupakan suatu gabungan dari bahan penyusun yang terdiri dari bahan semen hidrolik (portland cement), agregat kasar, agregat halus, air, dan bahan tambah. Umumnya penggunaan beton dimulai dari konstruksi bawah sampai konstruksi atas. Pada penggunaan di konstruksi bawah, beton akan berada dalam lingkungan yang beragam, salah satunya adalah lingkungan agresif seperti air payau. Air payau adalah campuran antara air tawar dan air laut (air asin). Jika kadar garam yang dikandung dalam satu liter air adalah antara 0,5 sampai 30 gram, maka air ini disebut air payau. Penelitian menggunakan air payau yang diambil dari 2 tempat berbeda yaitu air payau kenjeran dan air payau mangrove dan dengan menggunakan metode eksperimen di laboratorium, dengan total benda uji beton sebanyak 60 sampel. Pengujian kuat tekan beton pada umur 7 hari, 14 hari, 21 hari, dan 28 hari, dengan diameter silinder 15 cm dan tinggi 30 cm, dengan mutu beton yang direncanakan f’c = 25 Mpa.Hasil Pengujian beton normal memiliki kuat tekan 25,93 MPa, pada beton dengan campuran air payau kenjeran memiliki kuat tekan 17,75 mengalami penurunan kuat tekan sebesar 31,54% dari beton normal, sedangkan pada beton dengan campuran air payau mangrove memiliki kuat tekan 18,84 MPa mengalami penurunan kuat tekan sebesar 27,36% dari beton normal. Pengujian model statistik yang digunakan adalah uji Chi-Kuadrat dan uji T menggunakan aplikasi SPSS. Kata kunci :Beton, air payau, kuat tekan beton